A feasibility study on Quikfix Co. an all-in-one home repair service provider - Carpio, Pepito Leo; Enriquez, Walter Anjo; Omega, Derek Jose; Reyes, Janina Elyse (Quezon City College of Engineering, University of the Philippines Diliman, 2009)
Everyone wants to live comfortably and stress-free in their own homes. But such a thing is hard to achieve when there is something which needs to be repaired. These repair concerns give additional burden to the residents in terms of the added cost, the safety hazard, and the discomfort. This paper is about the feasibility study conducted for Quikfix Co., a home repair service company which provides home improvement and repair solutions to almost every repair problems commonly encountered in any households. The range of services it offers mainly involves carpentry, plumbing, electrical, and appliance repair. The market for a home repair service was first established where it was determined that there a large market for these type of service. The target market will be Quezon City residents from the A and B classes, these amounts to over 1,000 households. However, the competitive rivalry in this industry is very stiff that's why Quickfix should always provide quality service with quick response time. The technical requirements for Quikfix Co. were then evaluated. Several suppliers were evaluated for the company's material needs. With the cost and the availability of needed items as the main considerations, it was found out that Handyman will be the company's supplier. The labor requirements will be fulfilled by hiring only certified individuals from technical schools offering repair courses. The facility will be placed in Libis, Quezon City after evaluating different sites in terms of cost and proximity to potential customers. The organizational structure of Quikfix Co. was designed. The organization will be divided into four main departments namely, (1) Finance, (2) Operations and Inventory Control, (3) Human resource, and (4) Marketing Procurement. The structure is effective in the sense that there is a clear designation of tasks the different sections: of the company. The employees should possess the necessary skills and qualities to effectively execute the tasks. The financial aspect of the project was then assessed. After identifying all project costs involved, it was found out that over Php 6.2 million as initial investment is needed. The operations can be supported in the beginning by applying for a bank loan. Aside from financial gains from the project, the social contributions of the project were also considered. The establishment of Quikfix Co. will provide up to a hundred jobs within the span of five years. The society will also benefit in terms of having the comfort of living in their own homes free from those unwanted repair problems. After the different aspects of the study were evaluated and considered, it was determined that all components yield favorable results and that all requirements were satisfied. It can be concluded that establishing Quikfix Co., an all-in-one home repair service provider, is very much feasible.
Submitted in partial fulfillment of the course requirements in IE 153 : Project development and management.
Keywords: Dwellings -- Maintenance and repair; Feasibility studies